Green Performance: Critical factors from Malaysian electrical and electronics suppliers - Shaharudin, Mohd Rizaimy; Abd Rahim, Saiful Azmir Kasdi; Zainoddin, Amir Imran; Ahmad Yazid, Noor Jasmina Natasha (Environment-Behaviour Proceedings Journal, 2024)
The objective of the study is to identify critical factors influencing suppliers’ environmental performance. Employing survey methodologies, a cross-sectional study was conducted, analysing 110 completed survey questionnaires from electrical and electronic suppliers. The findings revealed that suppliers’ green performance is significantly influenced by quality practices, technical competence, a green image, and environmental management, although not by pollution control. In light of the growing importance of environmental achievements for market competitiveness, these results offer valuable insights for manufacturers seeking to enhance suppliers’ green performance. Future studies should explore additional crucial factors impacting suppliers’ environmental accomplishments.